Korrekcija techniki plavanija brassom na osnove optimizacii kinematiceskich charakteristik dviženij nogami - Gusev, A. V.; Kondakov, V. L.; Samus, A. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article presents the research aimed at the scientific justification and experimental study of the correction technique for the breaststroke swimming techniques based on the optimization of kinematic and dynamic characteristics. The developed technique helps to increase the efficiency of the technique of breaststroke swimming while decreasing the resistance forces by reducing the distance of the breeding of the knees when pulling the legs to the pelvis before repulsion; it reduces the variations of the intracyclic speed.